Assessing the Predictive Power of PIRCHE-II Scores for the Development of De Novo Donor-Specific Antibodies After Simultaneous Pancreas-Kidney Transplantation - Francesca Raineri; Lukas Frischknecht; Jakob Nilsson; Fabian Rössler; Claudia Cavelti-Weder; Seraina von Moos; Seraina von Moos; Thomas Schachtner (Transplant International)
The molecular HLA epitope mismatch is an advanced measure for developing de novo donor-specific antibodies (dnDSA) after kidney transplantation. Its relevance in simultaneous pancreas/kidney transplant recipients (SPKTRs) remains unclear. We investigated dnDSA development in 72 SPKTRs and 383 kidney transplant recipients (KTRs) and used the Predicted Indirectly Recognizable HLA-Epitopes (PIRCHE-II) algorithm to calculate the mismatch load of HLA-derived epitopes in total, per HLA-class, and per HLA-locus. At 1 year post-transplant, SPKTRs exhibited an increased dnDSA incidence (11.2% vs. 3.1%, p = 0.011); but not at 10 years post-transplant. In SPKTRs, preformed DSA (HR 2.872, p = 0.039) and younger donor age (HR 0.943, p = 0.017) were independent risk factors for developing dnDSA. PIRCHE-II scores for HLA-DQ correlated with dnDSA development upon univariate analysis (p = 0.044). Among 455 KTRs/SPKTRs, multivariate analysis identified PIRCHE-II scores for HLA-DQ (HR 1.023, p = 0.025) and ciclosporine use (HR 2.440, p = 0.001) as independent predictors of dnDSA development. Simultaneous pancreas/kidney transplantation (SPK) was an independent risk factor in case of preformed DSA only (HR 2.782, p = 0.037). High PIRCHE-II scores for HLA-DQ are crucial for dnDSA development in both SPKTRs and KTRs. The lack of an independent association of total PIRCHE-II scores urges caution in implementing it in post-transplantation risk assessment.